Information systems for knowledge workers support - Rizun, Mariia (Business Informatics, 2017)
The paper is dedicated to the Knowledge Management Information Systems (KMIS) as support tools for knowledge workers (KWs) activities. The general aim of the paper is to analyze the currently used systems and find out whether they meet all the requirements of KWs in the Knowledge Management (KM) process. To clarify the subjects of the research, the notions KWs and KMIS are presented in the form of concept maps. To specify the demands of KWs as for the software tools that assist them in the process of KM, the typology of KWs tasks was developed. Operation of the KMIS is examined from the point of view of their compatibility with the tasks and actions performed by KWs – in order to enhance functionality of the existing systems. The systems are divided into groups, each of them matched with a particular KM task. A case study of the open-source platform Moodle is given as a justification of the fact that support quality of KMIS presently requires improvements
Informatyka Ekonomiczna = Business Informatics, 2017, Nr 4 (46), s. 121-130
Keywords: knowledge management; knowledge worker; knowledge action; Knowledge Management Information System; zarządzanie wiedzą; pracownik wiedzy; działania pracowników wiedzy; systemy informatyczne zarządzania wiedzą